Reciting Surah Al-Ikhlas, Al-Falaq, An-Nas: A Study of Living Qur'an at Madrasah Tsanawiyah Hasanuddin Sidoarjo - Mustofa, Aan Najib; Fadilah, Nurul (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This research is exploratory qualitative research to discover the concept of Quranic life and its application in MTs Model Hasanuddin School, Sidoarjo. Data was collected through interviews with school principals, and the data obtained were processed and given results. After observing and discussing with the Public Relations Director of MTs Hasanuddin, it was discovered that a live Quran was being used in this school. Upon arrival at school, students recite Shalawat Jibril twenty-one times, Surah Al-Ikhlas three times, Al-Falaq once, and surah An-Nas once. The purpose is to shade teachers and students with divine light, and they are not used to doing negative. The Living Quran is used, and teachers and students are accustomed to reading the shalawat Jibril, surah Al-Ikhlas, Al-Falaq, and surah An-Nas. The result is that they can turn calm, non-violent, and more mature according to school rules. In conclusion, the teachers and students of MTs. Model Hasanuddin, after getting used to reading it, gets Allah’s blessing and can create an Islamic environment.